Computed DWI MRI Results in Superior Capability for N‐Stage Assessment of Non‐Small Cell Lung Cancer Than That of Actual DWI, STIR Imaging, and FDG‐PET/CT - Ohno, Yoshiharu; Yui, Masao; Takenaka, Daisuke; Yoshikawa, Takeshi; Koyama, Hisanobu; Kassai, Yoshimori; Yamamoto, Kaori; Oshima, Yuka; Hamabuchi, Nayu; Hanamatsu, Satomu; Obama, Yuki; Ueda, Takahiro; et al. (Journal of magnetic resonance imaging, 2023)
Background Computed diffusion‐weighted imaging (cDWI) is a mathematical computation technique that generates DWIs for any b‐value by using actual DWI (aDWI) data with at least two different b‐values and may improve differentiation of metastatic from nonmetastatic lymph nodes. Purpose To determine the appropriate b‐value for cDWI to achieve a better diagnostic capability for lymph node staging (N‐staging) in non‐small cell lung cancer (NSCLC) patients compared to aDWI, short inversion time (TI) inversion recovery (STIR) imaging, or positron emission tomography with 2‐[fluorine‐18] fluoro‐2‐deoxy‐d‐glucose combined with computed tomography (FDG‐PET/CT). Study Type Prospective. Subjects A total of 245 (127 males and 118 females; mean age 72 years) consecutive histopathologically confirmed NSCLC patients. Field Strength/Sequence A 3 T, half‐Fourier single‐shot turbo spin‐echo sequence, electrocardiogram (ECG)‐triggered STIR fast advanced spin‐echo (FASE) sequence with black blood and STIR acquisition and DWI obtained by FASE with b‐values of 0 and 1000 sec/mm2. Assessment From aDWIs with b‐values of 0 and 1000 (aDWI1000) sec/mm2, cDWI using 400 (cDWI400), 600 (cDWI600), 800 (cDWI800), and 2000 (cDWI2000) sec/mm2 were generated. Then, 114 metastatic and 114 nonmetastatic nodes (mediastinal and hilar lymph nodes) were selected and evaluated with a contrast ratio (CR) for each cDWI and aDWI, apparent diffusion coefficient (ADC), lymph node‐to‐muscle ratio (LMR) on STIR, and maximum standard uptake value (SUVmax). Statistical Tests Receiver operating characteristic curve (ROC) analysis, Youden index, and McNemar's test. Results Area under the curve (AUC) of CR600 was significantly larger than the CR400, CR800, CR2000, aCR1000, and SUVmax. Comparison of N‐staging accuracy showed that CR600 was significantly higher than CR400, CR2000, ADC, aCR1000, and SUVmax, although there were no significant differences with CR800 (P = 0.99) and LMR (P = 0.99). Data Conclusion cDWI with b‐value at 600 sec/mm2 may have potential to improve N‐staging accuracy as compared with aDWI, STIR, and PET/CT. Evidence Level 2 Technical Efficacy Stage 2